A polyacrylonitrile / polybenzoxazine aerogel and a method of making the same

CN117384419BActive Publication Date: 2026-10-30CIVIL AVIATION FLIGHT UNIV OF CHINA
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311486139.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-09
Publication Date
2026-10-30
Estimated Expiration
2043-11-09

AI Technical Summary

Technical Problem

[0006]本发明的目的在于:为了解决现有的单一的聚丙烯腈气凝胶的力学性能较差且吸附能力有限,难以实现高吸附的问题,本发明提供一种聚丙烯腈/聚苯并噁嗪气凝胶及其制备方法,具有高吸附量,可用于油水分离,回弹性好,具有超疏水性能,可用于油水分离领域

Benefits of technology

[0022]1.本发明所涉及的一种聚丙烯腈/聚苯并噁嗪气凝胶的制备方法,使用静电纺丝和冷冻干燥技术制备聚丙烯腈/聚苯并噁嗪气凝胶,将二维聚丙烯腈纤维膜、苯并噁嗪使用均质法共混,有效提高了聚丙烯腈气凝胶的力学性能和吸附性能,使其具有良好的回弹性,同时保证了气凝胶的低密度及疏水性能和尺寸稳定性。选择低成本、容易获得和具有良好可纺性的高分子聚合物聚丙烯腈(PAN)为静电纺基体,作为三维网络的骨架,苯并噁嗪在开环聚合反应中无小分子物释放,选择苯并噁嗪作为交联剂能够提高气凝胶材料的力学性能,在高温下引发苯并噁嗪单体的聚合反应,得到机械性能较好的气凝胶材料。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117384419B_ABST
    Figure CN117384419B_ABST
Patent Text Reader

Abstract

The application discloses a kind of polyacrylonitrile / polybenzoxazine aerogel and preparation method thereof, it is related to polyacrylonitrile aerogel preparation technical field, solve the mechanical property of single polyacrylonitrile aerogel, poor, hydrophobic performance and limited adsorption capacity, it is difficult to realize high adsorption problem.The preparation method includes the following steps: S1, raw material is stirred at first preset temperature to obtain polyacrylonitrile spinning solution;S2, polyacrylonitrile spinning solution is electrospun, to obtain polyacrylonitrile fiber membrane;S3, take polyacrylonitrile fiber membrane, benzoxazine is added into tert-butyl alcohol solution, stirring to obtain suspension;S4, suspension is frozen first, then freeze-dried, and then solidified at second preset temperature, to obtain finished product.Also provide polyacrylonitrile / polybenzoxazine aerogel prepared by the above preparation method.The prepared aerogel has high adsorption capacity, good resilience, has super-hydrophobic property, and can be used in oil-water separation field.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polyacrylonitrile aerogel preparation technology, specifically to a polyacrylonitrile / polybenzoxazine aerogel and its preparation method. Background Technology

[0002] With the rapid development of global industrial technology, large amounts of oily wastewater are being discharged from industries, and oil spills are occurring frequently, leading to various oil pollution problems. Aerogels are typical three-dimensional porous materials, and due to their low density, large surface area, high porosity, large adsorption capacity, and self-supporting structure, they are considered one of the most attractive adsorbents.

[0003] Currently, single polyacrylonitrile aerogels exhibit poor mechanical properties, require further improvement in hydrophobicity, and have limited adsorption capacity, making it difficult to achieve high adsorption and posing numerous challenges in the field of oil-water separation. While existing technologies have addressed these shortcomings, they all possess significant limitations.

[0004] For example, the invention patent with publication number CN115895159A proposes a method for preparing a polyacrylonitrile / polyimide macroporous oriented composite aerogel. Polyimide is selected as the binder and crosslinking agent, thereby giving the aerogel good resilience properties. However, the polyimide needs to be amidated, and the macroporous orientation requires directional freezing using the orientation ice crystal template method, making the preparation process relatively complex.

[0005] Therefore, the poor mechanical properties and limited adsorption capacity of single polyacrylonitrile aerogels, making it difficult to achieve high adsorption, remain unresolved. Furthermore, the supercritical drying technology used for aerogels requires high temperatures and pressures; these high-temperature, high-pressure conditions, along with the flammability of organic solvents, severely limit its large-scale industrial applications. The sol-gel method for preparing aerogels may also result in non-gelation, leading to preparation failure. Summary of the Invention

[0006] The purpose of this invention is to address the problem that existing single polyacrylonitrile aerogels have poor mechanical properties and limited adsorption capacity, making it difficult to achieve high adsorption. This invention provides a polyacrylonitrile / polybenzoxazine aerogel and its preparation method, which has high adsorption capacity, can be used for oil-water separation, has good resilience, and has superhydrophobic properties, making it suitable for the field of oil-water separation.

[0007] To achieve the above objectives, the present invention specifically adopts the following technical solution:

[0008] A method for preparing polyacrylonitrile / polybenzoxazine aerogel includes the following steps:

[0009] S1. Take the raw materials and stir them at the first preset temperature to obtain a polyacrylonitrile spinning solution;

[0010] S2. Electrospinning the polyacrylonitrile spinning solution to obtain a polyacrylonitrile fiber membrane;

[0011] S3. Take polyacrylonitrile fiber membrane and benzoxazine and add them to tert-butanol solution, stir to obtain suspension;

[0012] S4. The suspension is first frozen and then freeze-dried, and then solidified at a second preset temperature to obtain the finished product.

[0013] Optionally, the raw material in step S1 is any one of N,N-dimethylformamide, N,N-dimethylacetamide, and dimethyl sulfoxide, as well as polyacrylonitrile powder.

[0014] Optionally, the relative molecular mass of the polyacrylonitrile powder is 50,000 to 250,000.

[0015] Optionally, the first preset temperature is 55-65°C.

[0016] Optionally, the specific parameters for spinning in S2 are: spinning solution flow rate of 0.01 to 0.075 mm / min, spinning voltage of 9 to 13 kV, spinning flywheel speed of 50 to 70 rpm, and receiving distance of 15 to 20 cm.

[0017] Optionally, the benzoxazine is any one of the following structures:

[0018]

[0019] Optionally, in step S4, the freezing time is 6 to 12 hours. Optionally, in step S4, the freeze-drying time is 24 to 36 hours. Optionally, the second preset temperature is 200 to 300°C.

[0020] The invention also provides a polyacrylonitrile / polybenzoxazine aerogel prepared by the above preparation method, wherein the aerogel has a maximum adsorption capacity of 54-157 g / g for solvents and oils.

[0021] Compared with the prior art, the advantages of the present invention are as follows:

[0022] 1. This invention relates to a method for preparing polyacrylonitrile / polybenzoxazine aerogel. The method utilizes electrospinning and freeze-drying techniques to prepare the aerogel. Two-dimensional polyacrylonitrile fiber membranes and benzoxazine are homogenized and blended, effectively improving the mechanical and adsorption properties of the polyacrylonitrile aerogel, giving it good resilience, while ensuring low density, hydrophobicity, and dimensional stability. Polyacrylonitrile (PAN), a low-cost, readily available, and spinnable polymer, is selected as the electrospinning matrix to serve as the framework of the three-dimensional network. Benzoxazine does not release small molecules during ring-opening polymerization. Using benzoxazine as a crosslinking agent improves the mechanical properties of the aerogel material. The polymerization of benzoxazine monomers is initiated at high temperatures, resulting in an aerogel material with good mechanical properties.

[0023] 2. This invention relates to a polyacrylonitrile / polybenzoxazine aerogel with high adsorption capacity, suitable for oil-water separation, good resilience, and superhydrophobic properties, making it applicable in the oil-water separation field. Electrospun fibers have micro-nano diameters, resulting in aerogels with uniform pore size, which limits their mechanical and adsorption properties, hindering further applications. The preparation method of this invention combines electrospinning and freeze-drying techniques to create an ultra-low-density three-dimensional fiber network with a highly porous structure, providing an effective solution for the efficient adsorption of lightweight oils and fats. Single polyacrylonitrile aerogels have poor adsorption capacity and mechanical properties. This invention improves mechanical properties by introducing the crosslinking agent benzoxazine, resulting in good elasticity. Furthermore, a homogenization method is used to blend the two materials, resulting in an aerogel material that simultaneously possesses superhydrophobic and thermal insulation properties. Attached Figure Description

[0024] Figure 1 This is a schematic diagram of the finished product of polyacrylonitrile / polybenzoxazine aerogel of Example 1 of the present invention.

[0025] Figure 2 The adsorption process of the polyacrylonitrile / polybenzoxazine aerogel of the present invention is described.

[0026] Figure 3 This is a schematic diagram showing the process and results of measuring the water contact angle of the polyacrylonitrile / polybenzoxazine aerogel in Example 1 of the present invention.

[0027] Figure 4 This is a schematic diagram showing the process and results of measuring the water contact angle of the polyacrylonitrile aerogel in the control group.

[0028] Figure 5 This is a schematic diagram of the compression experiment of the polyacrylonitrile / polybenzoxazine aerogel in Example 2 of the present invention.

[0029] Figure 6This is a schematic diagram showing the data of different compression deformations of the polyacrylonitrile / polybenzoxazine aerogel in Example 2 of the present invention.

[0030] Attached image captions: Figure 5 In Chinese, "compress" means to compress and "release" means to release and bounce. Figure 6 In this context, "Compress stress" refers to compressive stress, "Compress strain" refers to compressive strain, "Loading" refers to applying pressure, and "Unloading" refers to not applying pressure.

[0031] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are some embodiments of the present invention, but not all embodiments.

[0032] Therefore, the following detailed description of the embodiments of the present invention is not intended to limit the scope of the claimed invention, but merely to illustrate selected embodiments of the invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention. Detailed Implementation

[0033] This invention provides a method for preparing polyacrylonitrile / polybenzoxazine aerogel, comprising the following steps:

[0034] S1. Take the raw materials and stir them at the first preset temperature to obtain a polyacrylonitrile spinning solution;

[0035] S2. Electrospinning the polyacrylonitrile spinning solution to obtain a polyacrylonitrile fiber membrane;

[0036] S3. Take polyacrylonitrile fiber membrane and benzoxazine and add them to tert-butanol solution, stir to obtain suspension;

[0037] S4. The suspension is first frozen and then freeze-dried, and then solidified at a second preset temperature to obtain the finished product.

[0038] It is understood that the preparation method of polyacrylonitrile / polybenzoxazine aerogel involved in this invention uses electrospinning and freeze-drying technology to prepare polyacrylonitrile / polybenzoxazine aerogel. The two-dimensional polyacrylonitrile fiber membrane and benzoxazine are blended by homogenization, which effectively improves the mechanical properties and adsorption properties of polyacrylonitrile aerogel, giving it good resilience, while ensuring the low density, hydrophobic properties and dimensional stability of the aerogel.

[0039] Polyacrylonitrile (PAN), a low-cost, readily available polymer with good spinnability, was selected as the electrospinning matrix to serve as the framework of the three-dimensional network. Benzoxazine does not release small molecules during ring-opening polymerization. Choosing benzoxazine as a crosslinking agent can improve the mechanical properties of aerogel materials. Pre-oxidation of polyacrylonitrile and polymerization of benzoxazine monomers were initiated at high temperatures to obtain aerogel materials with good mechanical properties.

[0040] In some embodiments of the present invention, in step S3, the molar ratio of polyacrylonitrile fiber membrane to benzoxazine is 5:2. It should be noted that this ratio can be adjusted; increasing the amount of benzoxazine added will increase the compressive strength of the aerogel.

[0041] In some embodiments of the present invention, the raw material in step S1 is any one of N,N-dimethylformamide, N,N-dimethylacetamide, and dimethyl sulfoxide, as well as polyacrylonitrile powder.

[0042] In some embodiments of the present invention, the relative molecular mass of the polyacrylonitrile powder is 50,000 to 250,000.

[0043] In some embodiments of the present invention, the first preset temperature is 55-65°C.

[0044] In some embodiments of the present invention, the specific parameters of spinning in S2 are as follows: the spinning solution flow rate is 0.01 to 0.075 mm / min, the spinning voltage is 9 to 13 kV, the spinning flywheel speed is 50 to 70 rpm, and the receiving distance is 15 to 20 cm.

[0045] In some embodiments of the present invention, the benzoxazine is any one of the following structures:

[0046]

[0047] In some embodiments of the present invention, in step S4, the freezing time is 6 to 12 hours.

[0048] In some embodiments of the present invention, in step S4, the freeze-drying time is 24 to 36 hours.

[0049] In some embodiments of the present invention, the second preset temperature is 200-300°C.

[0050] The invention also provides a polyacrylonitrile / polybenzoxazine aerogel prepared by the above preparation method, wherein the aerogel has a maximum adsorption capacity of 54-157 g / g for solvents and oils.

[0051] It is understood that the aerogel of this invention has a high adsorption capacity, can be used for oil-water separation, has good resilience, and good thermal insulation properties. The electrospun fibers have micro-nano diameters, resulting in aerogels with uniform pore size, which limits their mechanical and adsorption properties and affects their further applications. The preparation method of this invention, combining electrospinning and freeze-drying techniques, can prepare an ultra-low density three-dimensional fiber network with a highly porous structure, providing an effective solution for the efficient adsorption of lightweight oils and fats. Single polyacrylonitrile aerogel materials have poor adsorption capacity and mechanical properties. This invention improves its mechanical properties by introducing a crosslinking agent, benzoxazine, resulting in good elasticity. Furthermore, by using a homogenization method to blend the two, the resulting aerogel material exhibits both superhydrophobic properties and good oil-water separation performance.

[0052] Example 1

[0053] 1.1 Preparation Operation

[0054] 12g of polyacrylonitrile powder was dissolved in 15mL of N,N-dimethylformamide (DMF) and stirred in a 60℃ oil bath for 6 hours to obtain a yellow, transparent PAN spinning solution. The solution was drawn into a 10mL medical syringe, and excess air was expelled before electrospinning. The spinning solution flow rate was 0.075mm / min, the spinning voltage was 12.6kV, the receiving distance between the syringe needle and the aluminum foil on the roller receiving device was 17cm, and the roller receiving device rotation speed was 50rpm. After electrospinning, the resulting polyacrylonitrile fiber membrane was removed from the aluminum foil after being allowed to stand and dry with residual solvent.

[0055] The PAN fiber membrane was cut into 1×1cm pieces. 2 Take a small piece (0.2g) of fiber membrane and 0.06g of BOZ-1 in a beaker, add 25mL of tert-butanol, and stir using a homogenizer at 10000rpm to obtain a uniformly dispersed suspension. Freeze the suspension in a refrigerator for 12 hours, then freeze-dry for 24 hours. Cure the freeze-dried sample at 235℃ under a nitrogen atmosphere for 2 hours to obtain a cured and crosslinked polyacrylonitrile / polybenzoxazine aerogel. Please refer to [link to relevant documentation]. Figure 1 , which is the aerogel obtained.

[0056] Example 2

[0057] 2.1 Preparation Operation

[0058] 12g of polyacrylonitrile powder was dissolved in 15mL of N,N-dimethylacetamide and stirred in an oil bath at 60℃ for 7h to obtain a yellow, transparent PAN spinning solution. The solution was drawn into a 10mL medical syringe, and excess air was expelled before electrospinning. The spinning solution flow rate was 0.075mm / min, the spinning voltage was 12.6kV, the receiving distance between the syringe needle and the aluminum foil on the roller receiving device was 17cm, and the roller receiving device rotation speed was 50rpm. After electrospinning, the obtained polyacrylonitrile fiber membrane was removed from the aluminum foil after being allowed to stand and dry with residual solvent.

[0059] The PAN fiber membrane was cut into 1×1cm pieces. 2 Take a small piece (0.2g) of fiber membrane and 0.04g of BOZ-3 and place them in a beaker. Add 25mL of tert-butanol and homogenize at 8000rpm for 15min to obtain a uniformly dispersed suspension. Freeze the suspension for 12 hours, then freeze-dry for 24 hours. Cure the freeze-dried sample at 200℃ for 2 hours under a nitrogen atmosphere to obtain a cured and crosslinked polyacrylonitrile / polybenzoxazine aerogel.

[0060] Example 3

[0061] 3.1 Preparation Operation

[0062] 12g of polyacrylonitrile powder was dissolved in 15mL of dimethyl sulfoxide and stirred in an oil bath at 60℃ for 8 hours to obtain a yellow, transparent PAN spinning solution. The solution was drawn into a 10mL medical syringe, and excess air was expelled before electrospinning. The spinning solution flow rate was 0.005mm / min, the spinning voltage was 12kV, the receiving distance between the syringe needle and the aluminum foil on the roller receiving device was 17cm, and the roller receiving device rotation speed was 50rpm. After electrospinning, the resulting polyacrylonitrile fiber membrane was removed from the aluminum foil after being allowed to stand and dry with residual solvent.

[0063] The PAN fiber membrane was cut into 1×1cm pieces. 2 Take a small piece (0.2g) of fiber membrane and 0.10g of BOZ-9 and place them in a beaker. Add 25mL of tert-butanol and homogenize at 7000rpm for 20 minutes to obtain a uniformly dispersed suspension. Freeze the suspension for 12 hours, then freeze-dry for 24 hours. Cure the freeze-dried sample at 300℃ for 4 hours under a nitrogen atmosphere to obtain a cured and crosslinked polyacrylonitrile / polybenzoxazine aerogel.

[0064] Example 4

[0065] 4.1 Preparation Operation

[0066] 12g of polyacrylonitrile powder was dissolved in 15mL of N,N-dimethylformamide (DMF) and stirred in an oil bath at 60℃ for 8 hours to obtain a yellow, transparent PAN spinning solution. The solution was drawn into a 10mL medical syringe, and excess air was expelled before electrospinning. The spinning solution flow rate was 0.075mm / min, the spinning voltage was 12.6kV, the receiving distance between the syringe needle and the aluminum foil on the roller receiving device was 17cm, and the roller receiving device rotation speed was 50rpm. After electrospinning, the resulting polyacrylonitrile fiber membrane was removed from the aluminum foil after being allowed to stand and dry with residual solvent.

[0067] The PAN fiber membrane was cut into 1×1cm pieces. 2 Take a small piece (0.2g) of fiber membrane and 0.06g of BOZ-10 and place them in a beaker. Add 25mL of tert-butanol and homogenize at 9000rpm for 15 minutes to obtain a uniformly dispersed suspension. Freeze the suspension for 12 hours, then freeze-dry for 24 hours. Cure the freeze-dried sample at 210℃ for 3 hours under a nitrogen atmosphere to obtain a cured and crosslinked polyacrylonitrile / polybenzoxazine aerogel.

[0068] Example 5

[0069] 5.1 Preparation Operation

[0070] 12g of polyacrylonitrile powder was dissolved in 15mL of N,N-dimethylformamide (DMF) and stirred in a 60℃ oil bath for 6 hours to obtain a yellow, transparent PAN spinning solution. The solution was drawn into a 10mL medical syringe, and excess air was expelled before electrospinning. The spinning solution flow rate was 0.075mm / min, the spinning voltage was 14kV, the receiving distance between the syringe needle and the aluminum foil on the roller receiving device was 20cm, and the roller receiving device rotation speed was 50rpm. After electrospinning, the resulting polyacrylonitrile fiber membrane was removed from the aluminum foil after being allowed to stand and dry with residual solvent.

[0071] The PAN fiber membrane was cut into 1×1cm pieces. 2 Take a small piece (0.2g) of fiber membrane and 0.07g of BOZ-13 and place them in a beaker. Add 25mL of tert-butanol and homogenize at 9000rpm for 12 minutes to obtain a uniformly dispersed suspension. Freeze the suspension for 10 hours, then freeze-dry for 26 hours. Cure the freeze-dried sample at 250℃ under a nitrogen atmosphere for 2 hours to obtain a cured and crosslinked polyacrylonitrile / polybenzoxazine aerogel.

[0072] Experimental Example 1: Comparison of performance parameters between polyhexahydrotriazine aerogel and conventional polyacrylonitrile aerogel

[0073] 1.1 Experimental Design

[0074] (1) The polyacrylonitrile / polybenzoxazine aerogels of Examples 1-4 were used as experimental groups 1-4, and commercially available polyacrylonitrile aerogels were selected as control groups. The adsorption capacity of solvents and oils and the density of the polyacrylonitrile / polybenzoxazine aerogels and polyacrylonitrile aerogels in experimental groups 1-4 and control groups were measured. For the measurement process, please refer to [link to relevant documentation]. Figure 2 .

[0075] 1.2 Test Results

[0076] Examples 1-4: The adsorption capacity and deformation of polyacrylonitrile aerogels in the control group for oils and organic solvents were determined. The results are shown in Table 1. (54-157)

[0077] Table 1 Performance parameters of polyacrylonitrile / polybenzoxazine aerogel

[0078] 1 Example 1 0.0176 54.3-87.9 2 Example 2 0.0165 61.6-115.6 3 Example 3 0.0168 58.5-92.8 4 Example 4 0.0157 67.3-157.2 5 Example 5 0.0161 72.3-134.2 6 control group 0.0152 32.3-56.9

[0079] 1.3 Results Analysis

[0080] As shown in Table 1, the polyacrylonitrile / polybenzoxazine aerogels prepared in Examples 1-3 of this invention all have high adsorption capacities, all above 54 g / g; while the adsorption capacity of the polyacrylonitrile aerogel in the control group is only 32.3 g / g. It can be seen that the polyacrylonitrile / polybenzoxazine aerogel prepared in this invention exhibits a higher oil adsorption capacity compared to the 32.3 g / g of the polyacrylonitrile aerogel in the control group.

[0081] Test Example 2: Determination of Contact Angle

[0082] 2.1 Experimental Design

[0083] The polyacrylonitrile / polybenzoxazine aerogel from Example 1 was used as experimental group 5, and commercially available polyacrylonitrile aerogel was selected as the control group. The contact angles of the aerogels in the experimental and control groups were measured. The measurement process can be found in [link to documentation]. Figure 3 and Figure 4 .

[0084] 2.2 Test Results

[0085] The measurement results are shown in Table 2.

[0086] Table 2. Determination of contact angle

[0087] 1 Experimental group 5 156 2 control group 106

[0088] 2.3 Results Analysis

[0089] As shown in Table 2, the polyacrylonitrile / polybenzoxazine aerogel prepared in Example 1 of this invention has a water contact angle as high as 156°, indicating good hydrophobic properties.

[0090] In contrast, the water contact angle of the polyacrylonitrile aerogel in the control group was only 106°.

[0091] It is evident that the polyacrylonitrile / polybenzoxazine aerogel prepared in this invention has a larger water contact angle and better hydrophobic properties compared to the control group polyacrylonitrile aerogel.

[0092] Experiment Example 3 Compression Experiment

[0093] 3.1 Experimental Design

[0094] The polyacrylonitrile / polybenzoxazine aerogel from Example 2 was used as a sample for compression testing. Data on the compression process and different compression deformations are shown below. Figure 5 and Figure 6 .

[0095] 3.2 Results Analysis

[0096] See Figure 5 It can be seen that the polyacrylonitrile / polybenzoxazine aerogel prepared in Example 2 of the present invention has good resilience and can return to its original state even when compressed to 60% of its original height.

[0097] Please combine Figure 6 The polyacrylonitrile / polybenzoxazine aerogel prepared by this invention has good resilience.

[0098] In summary, based on the performance comparison test in Example 1, the aerogel of the present invention does indeed have a higher adsorption capacity for oils and organic solvents and a lower density. Furthermore, based on the water contact angle measurement in Example 2, the aerogel of the present invention also has a larger water contact angle, indicating better hydrophobic properties. In addition, based on the compression test in Example 3, the aerogel of the present invention exhibits good resilience.

[0099] As can be seen, the preparation method of polyacrylonitrile / polybenzoxazine aerogel involved in this invention uses electrospinning and freeze-drying technology to prepare polyacrylonitrile / polybenzoxazine aerogel. The two-dimensional polyacrylonitrile fiber membrane and benzoxazine are blended by homogenization, which effectively improves the mechanical properties and adsorption properties of polyacrylonitrile aerogel, giving it good resilience, while ensuring the low density, hydrophobic properties and dimensional stability of the aerogel.

[0100] The above embodiments are merely one implementation of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the present invention. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this patent should be determined by the appended claims.

Claims

1. A method for preparing polyacrylonitrile / polybenzoxazine aerogel, characterized in that, Includes the following steps: S1. Take any one of N,N-dimethylformamide, N,N-dimethylacetamide, and dimethyl sulfoxide, and polyacrylonitrile powder; stir at 55~65℃ to obtain a polyacrylonitrile spinning solution. S2. Electrospinning is performed on the polyacrylonitrile spinning solution. The spinning solution flow rate is 0.01~0.075 mm / min, the spinning voltage is 9-13 kV, the spinning flywheel speed is 50~70 rpm, and the receiving distance is 15~20 cm; a polyacrylonitrile fiber membrane is obtained. S3. Take polyacrylonitrile fiber membrane and benzoxazine and add them to tert-butanol solution, stir to obtain suspension; S4. Freeze the suspension first, then freeze-dry it, and then solidify it at 200~300℃ to obtain the finished product. The freezing time is 6~12 hours and the freeze-drying time is 24~36 hours. The benzoxazine is any one of the following structures: 。 2. The method for preparing a polyacrylonitrile / polybenzoxazine aerogel according to claim 1, characterized in that, The relative molecular mass of the polyacrylonitrile powder is 50,000 to 250,000.

3. A polyacrylonitrile / polybenzoxazine aerogel prepared by the preparation method according to any one of claims 1-2, characterized in that, The aerogel has a maximum adsorption capacity of 54~157 g / g for solvents and oils.

Citation Information

Patent Citations

  • Polyacrylonitrile-polyimide macroporous oriented nanofiber composite aerogel as well as preparation method and application thereof

    CN115895159A

  • Preparation method of efficient oil-absorbing nanofiber aerogel

    CN111135771A